Flower exports in Colombia: a theoretical perspective - Mosquera Osorio, Juan José; Díaz Cardona, Paulina; Gómez Montoya, Jaydher Stiven; Vasquez, Miguel Ángel; Montoya Lopez, Susana (Universidad Francisco de Paula Santander, 2025)
Colombia stands out as the second-largest flower exporter worldwide, thanks to climatic factors, the use of greenhouse technologies, good agricultural practices, free trade agreements, collaboration between different public-private entities, and associations such as Asocolflores, which have allowed Colombian floriculture to maintain its competitiveness and export its production to foreign markets. The aim is to highlight the success factors, the problems faced, and the challenges that must be addressed. The research found that, in order to consolidate its position in the international market, Colombia must focus on improving logistics and communication processes within the supply chain to reduce costs and losses, maintain product quality, increase customer satisfaction, and increase competitiveness. From a theoretical perspective, the study seeks to establish the success factors that have allowed the floriculture sector to position itself as the second-largest producer worldwide.